Upaya Guru Mata Pelajaran IPS dalam Menanamkan Karakter Disiplin dan Tanggung Jawab Siswa - Amiruddin Amiruddin; Muhammad Widda Djuhan (Institut Agama Islam Negeri Ponorogo, 2021)
The background of this research begins with the finding of a lack of discipline and responsibility in class VIII C students of SMP Negeri 1 Jenangan. From the results of observations carried out by researchers on October 17 and October 24, 2020, it was found that 53% of students from class VIII C, namely 30 students did not do assignments in Integrated Social Studies subjects. This study aims to identify and analyze the efforts of social studies teachers in instilling the character of discipline and responsibility in students through integrated social studies learning in class VIII C of SMP Negeri 1 Jenangan. This study used qualitative research methods. The analytical technique used in this research is descriptive analysis technique. The results of the study found that the efforts of social studies teachers in instilling the character of discipline and responsibility were through the principle of Contextual Teaching and Learning (CTL) in which the teacher linked the material he studied with students' real world situations. Some of the obstacles in inculcating the character of discipline and responsibility, which include a) family factors, b) environmental factors, c) online learning, d) factors from students. While the solution to the obstacles in planting the character of discipline and responsibility is through, a) Control from the principal, b) Active role of teachers.